PENGARUH KINERJA KEUANGAN MELALUI HARGA SAHAM TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR INDUSTRI HOTEL, RESTORAN, DAN PARIWISATA YANG TERDAFTAR DI BEI TAHUN 2019-2020 - Wahida, Zinta Nur; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
The Covid-19 pandemic also has a negative impact on companies such as a decrease in stock prices and company financial performance which can affect company value. This study aims to determine the effect of financial performance on firm value through stock prices as an intervening variable. The population in this study are all sub-sector companies of the hotel, restaurant and tourism industry. The sample of this research used purposive sampling technique. Data analysis and hypothesis testing used the Structural Equation – Partial Least Square (PLS-SEM) model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that financial performance has a negative but significant effect on stock prices, financial performance has a significant positive effect on firm value, stock prices have a significant positive effect on firm value. The results of the indirect effect hypothesis test show that financial performance has a negative and insignificant effect on firm value through stock prices.